Pengaruh Corporate Governance Terhadap Penghindaran Pajak - Damara, Meridipa; Chandra, Novrina; Afni, Zalida (Jurusan Akuntansi Politeknik Negeri Padang, 2025)
This study aims to obtain empirical evidence whether corporate governance represented by the board of commissioners, institutional ownership, audit committee and independent commissioners can influence tax avoidance behavior in a company. In this study, the measuring instrument used to measure tax avoidance behavior is the Cash Effective Tax Rate (CETR). The object of research in this study is all non-cyclical consumer sector companies listed on the IDX from 2021 to 2023. In this study, the technique used to determine the sample to be studied was by using the purposive sampling technique, from 128 non-cyclical consumer companies listed on the IDX within a period of one year, the number of samples that met the requirements was 62 companies. The research data in this study were obtained from the financial statements of non-cyclical consumer sector companies and in this study the data will be analyzed using panel data regression assisted by using the STATA application. The results obtained from this study indicate that corporate governance represented by the board of commissioners, institutional ownership, audit committee and independent commissioners has no effect on corporate tax avoidance behavior.